Three‐Dimensional Power Doppler Vascularization in Women With Ovarian Endometriomas and Relationship With Associated Painful Symptoms. (27th May 2017) - Rizzello, Francesca; Capezzuoli, Tommaso; D'Amato Scherbatoff, Ippolita; Cozzolino, Mauro; Gandini, Loredana; Coccia, Maria Elisabetta
Abstract : Objectives: The objective of the study was to evaluate the correlation between endometrioma‐associated pain and lesion vascularization as measured with 3‐dimensional power Doppler transvaginal sonography. Methods: Endometriomas were examined, and 4 indices were obtained: mean grayness, flow index, vascularization index, and vascularization‐flow index. Dysmenorrhea, chronic pelvic pain, and dyspareunia were analyzed in terms of severity, presence/absence, and duration. Results: Twenty‐nine women were selected. The univariable association of painful symptoms in terms of presence/absence and duration was low with the exception of mean grayness with the presence of chronic pelvic pain (β = –0.106; P  = .047; 95% confidence interval, 0.810 to 0.998). The R 2 value increased to 0.226 for dysmenorrhea (β = –0.475; P  = .029) when analyzing the association between the vascularization index and the severity of painful symptoms. The visual analog scale scores for chronic pelvic pain and dyspareunia were higher ( R 2  = 0.300; β = –0.547 and –0.548, respectively; P  = .028 and .053). Conclusions: We observed an inverse association between the severity of pain and endometrioma vascularization. Further larger studies are required to confirm our findings.